COVID-19 pandemic exposes the vulnerability of the sharing economy: a novel accounting framework. Issue 5 (4th May 2022) - Chen, Guangwu; Cheng, Mingming; Edwards, Deborah; Xu, Lixiao
Abstract: The outbreak of the COVID-19 pandemic has resulted in a global economic recession, but little is known about the impact it has had on the informal economy, including the peer-to-peer rental market. This study assessed the financial loss of Airbnb listings for its hosts in Greater Sydney, Australia. Findings show that comparing August 2020 to January 2020, the pandemic resulted in 89.5 per cent income loss for Airbnb hosts (about 14 million) with hosts suffering about 6.5 times more than the Airbnb platform itself. However, many Airbnb hosts are not eligible for the financial aid being offered by the NSW State Government or the Australian Federal Government. The study further demonstrates the vulnerability of the sharing economy during a time of crisis. It contributes empirical evidence to the widening public debate on the sharing economy's contribution to sustainable tourism and decent work (SDG 8), and reduced inequalities (SDG 10), and, most importantly, it raises concerns over taxation and social protections for informal employees. Methodologically, this study contributes to the literature by presenting a comprehensive income accounting framework to analyse this segment of the workforce's financial performance, which can serve as benchmark for tax estimation and financial aids.